2017
DOI: 10.1016/j.jtho.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 Is Altered by Copy Number Loss, Mutation, and/or Loss of Protein Expression in More Than 70% of Malignant Peritoneal Mesotheliomas

Abstract: As in pleural mesothelioma, inactivation of BAP1 is frequent in peritoneal mesotheliomas. We found that BAP1 protein nuclear expression is a good prognostic factor and a more reliable marker for the complete loss of BAP1 activity than mutation or copy number loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…11,12 The BAP1 mutation in our case was not a truncating but a missense mutation, which is in line with previous reports. 12,13 In keeping with these data, we observed a selective loss of BAP1 expression in the tumor cells that may be explained by somatic ploidy including loss of the wild-type allele. Coverage data support this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…11,12 The BAP1 mutation in our case was not a truncating but a missense mutation, which is in line with previous reports. 12,13 In keeping with these data, we observed a selective loss of BAP1 expression in the tumor cells that may be explained by somatic ploidy including loss of the wild-type allele. Coverage data support this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…This idea must be viewed in light of the fact that 13 of the 23 subjects (56%) had a second malignancy, so the apparent longer survivals may reflect a lead time bias for subjects undergoing frequent medical surveillance. However, studies on mesotheliomas with somatic BAP-1 mutations (eg, Leblay et al 111 ) have also found that such tumors are associated with longer survival, so loss of BAP-1 may in fact confer a better prognosis.…”
Section: Bap-1 Cancer-predisposition Syndromementioning
confidence: 99%
“…In addition, inactivating mutations of neurofibromin 2 ( NF2 ) and cyclin-dependent kinase inhibitor 2A ( CDKN2A ) are also relatively common, while other mutations are rare. Previous studies in PeM [1118] have only focused on genomic information; therefore, the downstream consequences of these genomic alterations are not well understood. Genome information coupled with transcriptome and proteome information is more likely to be successful in revealing potential therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%